An ontology engineering approach for knowledge discovery from data in evolving domains - Gottgtroy, P; Kasabov, N; Macdonell, S (WIT Press/COPPE/Federal University of Rio de Janeiro, 2004)
Knowledge discovery in evolving domains presents several challenges in information extraction and knowledge acquisition from heterogeneous, distributed, dynamic data sources. We define an evolving process if the process is developing, changing over time in a continuous manner. Examples of such domains include biological sciences, medical sciences, and social sciences, among others. This paper describes research in progress on a new methodology for leveraging the semantic content of ontologies to improve knowledge discovery in complex and dynamical domains. We consider in this initial stage the problem of how to acquire previous knowledge from data and then use this information in the context of ontology engineering.